Hubungan Pola Asuh Orang Tua dengan Tingkat Kepercayaan Diri Remaja : Relationship Between Parenting Styles And The Lever Of Self-Confidence Of Adolescents - Deisya Ajrina Putri Salsabila, Zahrina; Ardian, Iwan; Nu’im Haiya, Nutrisia; Rismatul Azizah, Intan (Jurnal Keperawatan Berbudaya Sehat, 2025)
Self-confidence is an important aspect of adolescent development. Adolescents with positive self-esteem tend to adapt more easily to their surroundings and have good academic performance. Self-confidence can be influenced by cultural factors, education, personal experiences, and family environment. Parents with a positive parenting style make children feel safe, valued, and capable of developing social skills. Positive parenting also helps adolescents cope with stress, anxiety, and other emotional problems. Positive parenting has a significant impact on children's growth and helps shape their morality. The research aims to assess the relationship between parenting styles and adolescent self-confidence using a questionnaire that can be completed by interested parents and adolescents. The research design is descriptive quantitative correlational with a cross-sectional approach. The number of respondents was 81 people, selected using purposive sampling technique. The chi-square statistical test findings of 0.001 with a p-value of 0.000 (p < 0.05) indicate a substantial correlation between adolescent self-confidence levels and parenting styles, demonstrating a strong impact of parenting on self-confidence development. Teenage self-confidence falls into the "fair" category, along with parenting styles. Parenting patterns require special attention for adolescents.